1999
DOI: 10.1038/sj.onc.1202644
|View full text |Cite
|
Sign up to set email alerts
|

In vivo analysis of the state of the human uPA enhancer following stimulation by TPA

Abstract: We have analysed in vivo the 72.0 kb enhancer of the human urokinase-type plasminogen activator (uPA) gene in HepG2 cells, in which gene expression can be induced by phorbol esters. The results reveal that, within the regulatory region, the enhancer, the silencer and the minimal promoter become hypersensitive to deoxyribonuclease I (DNase I) upon induction of transcription. The hypersensitivity of the enhancer can be reversed after removal of the inducer. In vivo footprinting analysis indicates that all the ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…5B). This is in agreement with our previous results showing the presence of a DNase I-hypersensitive site on the uPA MP in PC3 cells (36). We also found that DAF-B is associated with HMGN1, another hallmark of transcriptionally active chromatin.…”
Section: Daf-a -B and -Bx Amplicons Represent Discrete Chromatin Stsupporting
confidence: 82%
“…5B). This is in agreement with our previous results showing the presence of a DNase I-hypersensitive site on the uPA MP in PC3 cells (36). We also found that DAF-B is associated with HMGN1, another hallmark of transcriptionally active chromatin.…”
Section: Daf-a -B and -Bx Amplicons Represent Discrete Chromatin Stsupporting
confidence: 82%
“…Interestingly, another hypersensitive site is present approximately 3.5 kb from the start of DNase I-digested and restricted DNA was fractionated on a 1% agarose gel in 0.5 ϫ TBE, transferred to positively charged nylon membrane, and probed as described. 29 (B) In PC3 cells the regulatory region of the uPA gene displays strong hypersensitivity to DNase I in proximity of the enhancer (ϳϪ1950) and the proximal promoter (ϳϪ86). The latter is completely absent in HeLa cells.…”
Section: Resultsmentioning
confidence: 99%
“…29 Nuclear extracts, EMSAs, and Western blots Nuclear extracts were obtained by the method of Dignam et al 30 Aliquots were frozen and kept at Ϫ80°C. EMSAs were performed as described 31 using approximately 10 g nuclear extract proteins/lane.…”
Section: Detection Of Dnase I Hypersensitive Sitesmentioning
confidence: 99%
“…1,[6][7][8][9][10][11][12][13][14][15][16][17][18][21][22][23][24]26,[35][36][37] The intervening sequence (Ϫ1879/Ϫ87) is not well characterized, although it is known to contain a putative negative regulatory element. 38 By comparing a uPA-nonproducing, primary tumor cell line (HeLa) with a constitutively high-level uPA-producing, metastatic cell line (PC3), we discovered that the uPA minimal promoter was active only in the latter.…”
Section: Discussionmentioning
confidence: 99%